A chemical 'explosion' triggered by an encounter between Indian and Chinese medical sciences: another look at the significances of the Sinhalese Monk Śākyamitra's (567?–668+) visit at Mount Wutai in 667. Issue 3 (3rd July 2018) - Chen, Jinhua
ABSTRACT: Chinese and Indian medical tradition, each had its own merits and their exchange dated back to ancient times and lasted over centuries. And their encounters often produced unexpected fruitful outcomes. This article discusses such an encounter through the life of the Southeast Asian monk Sākyamitra. The case of Sākyamitra reminds us that the exchange between China and India did not take place only in the domain of the religion —and certainly not only within Buddhism.  The fact that Sākyamitra could assume the position of the Interior Palace Servitor in the Tang court, not only hinged on (or perhaps was merely related to) his reputation as a Buddhist master, but also depended on his exceptional medical aptitude. This observation is especially true when we consider his pilgrimage to Mount Wutai, which might not have been a pilgrimage simply for his own sake. Nor was he obligated by his role in the priest-patron relationship with China, to fashion Mount Wutai into a central sacred land of the Buddhist world. Circumstantial evidence shows that this pilgrimage was at least partially motived by his goal of looking for an ingredient essential for concocting the immortal elixir for Emperor Gaozong of Tang --- saltpeter, also a key ingredient in the gunpowder, which ranks among the Four Great Inventions of China.